2022
DOI: 10.3390/ijerph19074288
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Non-Nutritional Strategies in Bodybuilding: Impact on Kidney Function

Abstract: Bodybuilders routinely engage in many dietary and other practices purported to be harmful to kidney health. The development of acute kidney injury, focal segmental glomerular sclerosis (FSGS) and nephrocalcinosis may be particular risks. There is little evidence that high-protein diets and moderate creatine supplementation pose risks to individuals with normal kidney function though long-term high protein intake in those with underlying impairment of kidney function is inadvisable. The links between anabolic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 103 publications
0
10
0
5
Order By: Relevance
“…The lack of adequate patient history reporting is demonstrated in the literature examining kidney disease in bodybuilders. A 2022 systematic review identified 13 papers (case studies and case series) which describe acute or chronic kidney injury or disease in a total of 75 bodybuilders [ 168 ]. Across studies, there is inconsistent reporting of protein intake and history of AAS, vitamins (and other supplements), diuretics, or nonsteroidal anti-inflammatory drug (NSAID) use.…”
Section: Challenges Of Identifying Primary Risk Factors In Bodybuildersmentioning
confidence: 99%
“…The lack of adequate patient history reporting is demonstrated in the literature examining kidney disease in bodybuilders. A 2022 systematic review identified 13 papers (case studies and case series) which describe acute or chronic kidney injury or disease in a total of 75 bodybuilders [ 168 ]. Across studies, there is inconsistent reporting of protein intake and history of AAS, vitamins (and other supplements), diuretics, or nonsteroidal anti-inflammatory drug (NSAID) use.…”
Section: Challenges Of Identifying Primary Risk Factors In Bodybuildersmentioning
confidence: 99%
“…Alguns fatores interferem nos valores de creatinina, tais como a idade, o sexo, a alimentação, o estado de saúde e a prática de exercícios físicos. (Dusse et al, 2017;Tidmas et al, 2022;Oh, 2020) A ureia não é um biomarcador sensível para avaliar filtração renal, visto que entre 40-70% retorna para o plasma sanguíneo através de difusão passiva tubular, dependente do fluxo de urina. Quando seus níveis estão aumentados na corrente sanguínea, tem-se a chamada azotemia ou uremia.…”
Section: Discussionunclassified
“…However, dehydration and sodium depletion resulting from fluid restriction is dangerous for training performance. 33 Psychologically, men with MD who do weight training non-professionally or non-competitively tend to yearn for approval or recognition for their appearance instead of their performance. 34 Body dissatisfaction, monitoring, and awareness are associated with irrational thoughts, perceptual distortion, and negative influences that damage a positive body image.…”
Section: Discussionmentioning
confidence: 99%